Liver biopsy in gall stone disease: a prospective study in patients undergoing cholecystectomy - Patel, Gaurav; Jain, Atul; Singh, Malwinder; Garg, Meenu; Karim, Tanweer; Dey, Subhajeet (International Surgery Journal, 2017)
Background: Cholelithiasis has affected mankind since many centuries. It not only affects the biliary tree but also has adverse effects on the hepatic parenchyma, which can get further complicated due to infected bile. Early intervention in these cases not only retards the unwanted effects but also prevents irreversible damage to liver. Aim of study was to see the effect of gallstone disease on liver in patients of GSD (Cholelithiasis, Chronic cholecystitis, CBD Stones). Methods: All patients being subjected for planned cholecystectomy were taken as subjects irrespective of age, sex and co-morbid conditions. Results: 90 patients were included in study and they were evaluated for secondary histopathological changes in liver. Abnormal liver histology was seen in 40% of the cases, with portal tract inflammation being the commonest abnormality seen in 24.4% of patients followed by fatty change (17.8%), cholestasis (10%), lobular parenchymal infiltration (8.9%) and one (1.1%) patient had fibrosis. Choledocholithiasis was associated with a greater incidence of positive bile culture (60%) and greater incidence of abnormal liver histology (80%). Conclusions: Gall stone disease cause significant changes in liver histology and these changes are more common in those patients having long duration of symptoms. In patients of choledocholithiasis incidence of infected bile and liver histology changes are more as compared to cholelithiasis with chronic cholecystitis.